Positive End-expiratory Pressure and Mechanical Power. (January 2019) - Collino, Francesca; Rapetti, Francesca; Vasques, Francesco; Maiolo, Giorgia; Tonetti, Tommaso; Romitti, Federica; Niewenhuys, Julia; Behnemann, Tim; Camporota, Luigi; Hahn, Günter; Reupke, Verena; Holke, Karin; et al.
Editor's Perspective: What We Already Know about This Topic: Positive end-expiratory pressure protects against ventilation-induced lung injury by improving homogeneity of ventilation, but positive end-expiratory pressure contributes to the mechanical power required to ventilate the lung What This Article Tells Us That Is New: This in vivo study (36 pigs mechanically ventilated in the prone position) suggests that low levels of positive end-expiratory pressure reduce injury associated with atelectasis, and above a threshold level of power, positive end-expiratory pressure causes lung injury and adverse hemodynamics Background: Positive end-expiratory pressure is usually considered protective against ventilation-induced lung injury by reducing atelectrauma and improving lung homogeneity. However, positive end-expiratory pressure, together with tidal volume, gas flow, and respiratory rate, contributes to the mechanical power required to ventilate the lung. This study aimed at investigating the effects of increasing mechanical power by selectively modifying its positive end-expiratory pressure component. Methods: Thirty-six healthy piglets (23.3 ± 2.3 kg) were ventilated prone for 50 h at 30 breaths/min and with a tidal volume equal to functional residual capacity. Positive end-expiratory pressure levels (0, 4, 7, 11, 14, and 18 cm H2 O) were applied to six groups of six animals. Respiratory, gas exchange, and hemodynamic variables were recorded every 6 h. Lung weight and wet-to-dry ratio were measured, and histologic samples were collected. Results: Lung mechanical power was similar at 0 (8.8 ± 3.8 J/min), 4 (8.9 ± 4.4 J/min), and 7 (9.6 ± 4.3 J/min) cm H2 O positive end-expiratory pressure, and it linearly increased thereafter from 15.5 ± 3.6 J/min (positive end-expiratory pressure, 11 cm H2 O) to 18.7 ± 6 J/min (positive end-expiratory pressure, 14 cm H2 O) and 22 ± 6.1 J/min (positive end-expiratory pressure, 18 cm H2 O). Lung elastances, vascular congestion, atelectasis, inflammation, and septal rupture decreased from zero end-expiratory pressure to 4 to 7 cm H2 O ( P < 0.0001) and increased progressively at higher positive end-expiratory pressure. At these higher positive end-expiratory pressure levels, striking hemodynamic impairment and death manifested (mortality 0% at positive end-expiratory pressure 0 to 11 cm H2 O, 33% at 14 cm H2 O, and 50% at 18 cm H2 O positive end-expiratory pressure). From zero end-expiratory pressure to 18 cm H2 O, mean pulmonary arterial pressure (from 19.7 ± 5.3 to 32.2 ± 9.2 mmHg), fluid administration (from 537 ± 403 to 2043 ± 930 ml), and noradrenaline infusion (0.04 ± 0.09 to 0.34 ± 0.31 μg · kg −1 · min −1 ) progressively increased ( P < 0.0001). Lung weight and lung wet-to-dry ratios were not significantly different across the groups. The lung mechanical power level that best discriminated between more versus less severe damage was 13 ± 1 J/min. Conclusions: Less than 7 cm H2 O positive end-expiratory pressure reduced atelectrauma encountered at zero end-expiratory pressure. Above a defined power threshold, sustained positive end-expiratory pressure contributed to potentially lethal lung damage and hemodynamic impairment. Abstract : This in vivo study (36 pigs mechanically ventilated in the prone position) suggests that low levels of positive end-expiratory pressure reduce injury associated with atelectasis, and above a threshold level of power, positive end-expiratory pressure causes lung injury and adverse hemodynamics.Supplemental Digital Content is available in the text.